2010
DOI: 10.3109/00016349.2010.512063
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved grief in women and men in Sweden three years after undergoing unsuccessful in vitro fertilization treatment

Abstract: Objective. To explore the experience of undergoing unsuccessful in vitro fertilization (IVF) treatment and of remaining childless 3 years after IVF in both women and men. Design. Qualitative-approach study. Sample. Ten women and nine men who had attended a public fertility clinic in Sweden. Methods. Individual qualitative semi-structured interviews were conducted with qualitative content analysis guiding the analysis. Results. Three years after the end of IVF treatment, most men and women were still processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 34 publications
5
50
0
1
Order By: Relevance
“…Infertile couples who had failed cycle experienced unresolved grief 3 years after treatment [17]. The findings of this review are consistent with the statement that the grieving process in the IVF cycle is often long [39].…”
Section: Long-term Emotional Reactions After Ivf Failuresupporting
confidence: 73%
See 4 more Smart Citations
“…Infertile couples who had failed cycle experienced unresolved grief 3 years after treatment [17]. The findings of this review are consistent with the statement that the grieving process in the IVF cycle is often long [39].…”
Section: Long-term Emotional Reactions After Ivf Failuresupporting
confidence: 73%
“…The findings showed that compared with the women who became parents, those women who remained childless had a higher level of stress (Perceived Stress Scale, PSS, m = 14.88 vs. A qualitative study conducted in Sweden revealed that the grieving process for both men and women was unresolved even 3 years after unsuccessful IVF [17]. Women were more likely to express grief than their husbands, who tended to assume the supportive roles and suppress their own feelings.…”
Section: Long-term Emotional Reactions After the Ivf Failurementioning
confidence: 99%
See 3 more Smart Citations